Predictors of Readmission, for Patients with Chronic Obstructive Pulmonary Disease (COPD) – A Systematic Review - Chow R; So OW; Im JHB; Chapman KR; Orchanian-Cheff A; Gershon AS; Wu R (International Journal of COPD, 2023)
Ronald Chow,1 Olivia W So,1 James HB Im,2 Kenneth R Chapman,1 Ani Orchanian-Cheff,1 Andrea S Gershon,3 Robert Wu1 1University Health Network, University of Toronto, Toronto, ON, Canada; 2The Hospital for Sick Children, Toronto, ON, Canada; 3Sunnybrook Health Sciences Centre, University of Toronto, Toronto, ON, CanadaCorrespondence: Ronald Chow, University Health Network, University of Toronto, Toronto, ON, Canada, Email ronald.chow@uhn.caIntroduction: Chronic obstructive pulmonary disease (COPD) is the third-leading cause of death globally and is responsible for over 3 million deaths annually. One of the factors contributing to the significant healthcare burden for these patients is readmission. The aim of this review is to describe significant predictors and prediction scores for all-cause and COPD-related readmission among patients with COPD.Methods: A search was conducted in Ovid MEDLINE, Ovid Embase, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials, from database inception to June 7, 2022. Studies were included if they reported on patients at least 40 years old with COPD, readmission data within 1 year, and predictors of readmission. Study quality was assessed. Significant predictors of readmission and the degree of significance, as noted by the p-value, were extracted for each study. This review was registered on PROSPERO (CRD42022337035).Results: In total, 242 articles reporting on 16,471,096 patients were included. There was a low risk of bias across the literature. Of these, 153 studies were observational, reporting on predictors; 57 studies were observational studies reporting on interventions; and 32 were randomized controlled trials of interventions. Sixty-four significant predictors for all-cause readmission and 23 for COPD-related readmission were reported across the literature. Significant predictors included 1) pre-admission patient characteristics, such as male sex, prior hospitalization, poor performance status, number and type of comorbidities, and use of long-term oxygen; 2) hospitalization details, such as length of stay, use of corticosteroids, and use of ventilatory support; 3) results of investigations, including anemia, lower FEV1, and higher eosinophil count; and 4) discharge characteristics, including use of home oxygen and discharge to long-term care or a skilled nursing facility.Conclusion: The findings from this review may enable better predictive modeling and can be used by clinicians to better inform their clinical gestalt of readmission risk.Keywords: predictors, readmission, chronic obstructive pulmonary disease